Modern real estate - Wurtzebach, Charles H.; Miles, Mike E.; Cannon, Susanne Ethridge (New York : John Wiley & Sons, 1994)
This book is divided into nine parts: The analytical framework; The legal environment; Valuation and the appraisal process; Marketing, Brokerage, and Management; Taxation; Investment analysis; Real Estate Development; and Public policy and Prospects for the Future.
Keywords: Economics; Business; United States; Real estate business; Real estate business -- United States